2013
DOI: 10.6061/clinics/2013(06)23
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and acute and subchronic toxicity studies of a standardized methanolic extract of Ficus deltoidea leaves

Abstract: OBJECTIVE:Ficus deltoidea leaves have been used in traditional medicine in Southeast Asia to treat diabetes, inflammation, diarrhea, and infections. The present study was conducted to assess the genotoxicity and acute and subchronic toxicity of a standardized methanol extract of F. deltoidea leaves.METHODS:Sprague Dawley rats were orally treated with five different single doses of the extract and screened for signs of toxicity for two weeks after administration. In the subchronic study, three different doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
3
41
0
1
Order By: Relevance
“…However, toxicological studies are required to determine the toxicity and thus establish criteria for the selection of a safe dose (Berenguer-Rivas et al, 2013;Farsi et al, 2013). The present study may represent the first study that demonstrates the absence of toxicity of the oil extracted from the pulp of A. aculeata, which can contribute to the safe use of this species.…”
Section: Resultsmentioning
confidence: 83%
“…However, toxicological studies are required to determine the toxicity and thus establish criteria for the selection of a safe dose (Berenguer-Rivas et al, 2013;Farsi et al, 2013). The present study may represent the first study that demonstrates the absence of toxicity of the oil extracted from the pulp of A. aculeata, which can contribute to the safe use of this species.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, the number of studies of plant extracts and their biological activities in humans and animals has increased (Farsi et al, 2013). However, the pharmacological studies reported have not been sufficient to validate the effects of these plant compounds on whole organisms (Reyes-García, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A 50 mg/kg pharmacological dose of betulinic acid was 20‐fold lower than the 1,000 mg AOT dose reported to be nontoxic (Jain et al, ). Hitherto, no AOT study for koetjapic acid has been documented for comparison at 50 mg/kg, kaempferol was 200‐fold less than the 10,000 mg/kg dose reported (Shih et al, ), vitexin was 100‐fold less than the 5,000 mg/kg tested (Farsi et al, ), and tiliroside was 20‐fold less than the 1,000 mg/kg tested (Nagatomo et al, ) for AOT studies where the doses tested were nontoxic. The above evidences therefore confirmed the safety of the doses for pharmacological studies of the isolated phytoconstituents in D .…”
Section: Discussionmentioning
confidence: 99%